Novel Biomarker-Targeted Therapies for Metastatic Colorectal Cancer - Barot, Shimoli V.; Kamath, Suneel D. (Digestive Disease Interventions, 2021)
Colorectal cancer (CRC) is one of the most common and fatal malignancies worldwide. Screening, surgery, and adjuvant therapy have proved efficacious in improving outcomes for early-stage disease. Despite decades of research efforts, cytotoxic chemotherapy has been the mainstay of treatment for metastatic disease and the prognosis remains unsatisfactory. Compelling evidence suggests that a fundamental reason for the limited success is the cancer's inherent dynamic heterogeneity, which is more predominant in late-stage disease. As our understanding of this molecular blueprint of CRC has evolved, a new avenue of targeted therapies has emerged. Beginning with epidermal growth factor receptor and vascular endothelial growth factor inhibitors, numerous targeted agents have been developed and investigated in large, multicenter, prospective clinical trials. Testing for mutations in RAS (KRAS and NRAS), BRAF, and HER2 and for mismatch repair/microsatellite instability and NTRK fusions has now been incorporated in the management guidelines, with additional biomarkers rapidly surfacing. As we enter the latest paradigm of precision oncology in CRC, this article will provide an overview of the different molecular subsets of CRC and the current biomarker-targeted therapies in the management of metastatic disease.
Keywords: colon cancer; targeted therapy; immunotherapy; biomarker; mutation